Urinary extracellular vesicles carry valuable hints through mRNA for the understanding of endocrine hypertension - Friso, Simonetta; Castagna, Annalisa; Mango, Gabriele; Olivieri, Oliviero; Pizzolo, Francesca (Frontiers in Endocrinology, 2023)
Urinary extracellular vesicles (uEVs), released from cells of the urogenital tract organs, carry precious information about originating tissues. The study of molecules transported through uEVs such as proteins, lipids and nucleic acids provides a deeper understanding of the function of the kidney, an organ involved in the pathogenesis of hypertension and a target of hypertension-mediated organ damage. Molecules derived from uEVs are often proposed for the study of disease pathophysiology or as possible disease diagnostic and prognostic biomarkers. Analysis of mRNA loading within uEVs may be a unique and readily obtainable way to assess gene expression patterns of renal cells, otherwise achievable only by an invasive biopsy procedure. Interestingly, the only few studies investigating transcriptomics of hypertension-related genes through the analysis of mRNA from uEVs are inherent to mineralocorticoid hypertension. More specifically, it has been observed that perturbation in human endocrine signalling through mineralcorticoid receptors (MR) activation parallels changes of mRNA transcripts in urine supernatant. Furthermore, an increased copy number of uEVs-extracted mRNA transcripts of the 11β-hydroxysteroid dehydrogenase type 2 (HSD11B2) gene were detected among subjects affected by apparent mineralocorticoid excess (AME), a hypertension-inducing autosomal recessive disorder due to a defective enzyme function. Moreover, by studying uEVs mRNA, it was observed that the renal sodium chloride cotransporter (NCC) gene expression is modulated under different conditions related to hypertension. Following this perspective, we illustrate here the state of the art and the possible future of uEVs transcriptomics towards a deeper knowledge of hypertension pathophysiology and ultimately more tailored investigational, diagnostic-prognostic approaches.